Fibrinolytic Bacterial Enzymes with Thrombolytic Activity - Kotb, Essam; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Stress, high blood pressure, smoking, pollution, fast foods, overweight, excessive travelling, surgery, less movement are common features in our modern life. These features are risky for blood clotting disorders. According to WHO, over 29% of the total mortalities worldwide are due to thrombosis. By the year, 2020 cardiovascular diseases (CVDs) may cause an estimated 25 million deaths per year, thus antithrombotic therapy is of great interest. The available thrombolytic agents such as urokinase are highly expensive, antigenic, quite unspecific, pyretogenic and hemorrhagenic. Therefore, the production of fibrinolysing enzymes, which rapidly dissolute thrombi within the vascular tree, without the detriments by microorganisms, as described in this book, is the desirable aim of today$1 (Bs research.s
Keywords: Medicine; Human physiology; Medical microbiology; Cardiology; Hematology; Biomedicine; Medical Microbiology; Hematology; Cardiology; Human Physiology; Electronic books